Bridging the Critical Thinking Gap: Evidence-Based Development of STEM-Based Project-Based Learning E-Modules for Vocational Education - N. Desti Pratiwi; Insih Wilujeng; Susilowati Susilowati (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
The rapid transformation brought by Industry 4.0 and Society 5.0 demands that vocational education graduates possess not only technical competencies but also higher-order thinking skills, particularly critical thinking. This study aims to analyse the level of vocational high school students’ critical thinking skills and to use the findings as an empirical basis for developing STEM-based Project-Based Learning (STEM-PjBL) e-modules. A quantitative descriptive design was employed involving 36 tenth-grade vocational students selected through random sampling. Data were collected using an essay-based test that measured five critical-thinking indicators: interpretation, analysis, evaluation, inference, and explanation. The results revealed that students’ overall critical thinking skills were at a moderate level, with strengths in interpretation and explanation, but weaknesses in analysis and inference. These findings indicate a significant gap in higher-order thinking skills, which are essential for solving real-world problems in vocational contexts. The study highlights the need for evidence-based instructional materials that specifically address these gaps. Therefore, the development of STEM-PjBL e-modules is proposed as a strategic approach to enhance students’ critical thinking through interdisciplinary, problem-based, and technology-supported learning. This research contributes to providing a diagnostic foundation for designing innovative learning resources in vocational education